2011
DOI: 10.5047/eps.2011.03.010
|View full text |Cite|
|
Sign up to set email alerts
|

Spectral peaks in electric field at resonance frequencies for seismically excited motion of ions in the Earth’s magnetic field

Abstract: Clear electric field variations have been observed during the passage of seismic wave. The most notable feature is circular polarization of electric field and it has been interpreted as reflecting circular motion of ions in groundwater under the Earth's magnetic field. We have called such a mechanism 'seismic dynamo effect' but more convincing evidence is required to support this mechanism. Here we show strong evidence in terms of transfer function relating the electric field to the ground velocity due to seis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…It is known that electric field variations, generated by circular motion of ions in groundwater under the Earth's geomagnetic field, are observed during the passage of seismic wave. This process is called "seismic dynamo effect" (e.g., Honkura et al, 2009), and the observed frequencies were higher than about 10 Hz (Kuriki et al, 2011). Though the magnetometer has enough sensitivity at 10-20 Hz, no such signatures are discernible in Fig.…”
Section: Initial Arrival and Northward Propagation Of Disturbancesmentioning
confidence: 99%
“…It is known that electric field variations, generated by circular motion of ions in groundwater under the Earth's geomagnetic field, are observed during the passage of seismic wave. This process is called "seismic dynamo effect" (e.g., Honkura et al, 2009), and the observed frequencies were higher than about 10 Hz (Kuriki et al, 2011). Though the magnetometer has enough sensitivity at 10-20 Hz, no such signatures are discernible in Fig.…”
Section: Initial Arrival and Northward Propagation Of Disturbancesmentioning
confidence: 99%
“…His numerical result showed that the coseismic magnetic field can reach the order of 0.1 nT, which is detectable. Recently, reports on the observed circularly polarized coseismic electric field [Honkura et al, 2009;Kuriki et al, 2011;Matsushima et al, 2013] provided evidences for the role of the Earth's magnetic field in generating EM disturbances. Moreover, observations of the tsunami-induced magnetic variations [Manoj et al, 2011;Toh et al, 2011;Utada et al, 2011;Ichihara et al, 2013] were further evidences which indicate that the conductive seawater moving across the Earth's magnetic field can also generate observable variations in the magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…It should be mentioned that there is another mechanism associated with the geomagnetic field. It is the so‐called “seismic dynamo effect” proposed by Honkura and his coauthors (Honkura et al., 2009; Kuriki et al., 2011; Matsushima et al., 2013) and caused by the motion and resonance of groundwater ions in the geomagnetic field. Honkura et al.…”
Section: Discussionmentioning
confidence: 99%